MANFAAT MEDIA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SD SELAMA PANDEMI COVID-19 - Mariana Jediut; Eliterius Sennen; Carolina Vebri Ameli (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
The purpose of this research is to describe the advantages of technology as a learning medium in increasing the learning motivation of elementary school students, and describe the forms of efforts of teachers in developing technology as an effective learning medium during Covid-19 pandemic. The type of research used in this study is qualitative research with library study. This research techniques were used: collect data, compile, use and interpret existing data.. The results showed that the advantages of learning medium technology were: 1) increasing interaction between teacher and students; 2) improving students' learning motivation; 3) facilitating teacers to deliver learning materials so that learning continues even if not done face-to-face; 4) As a medium of interaction between teachers and students during online learning; 5) Be a medium of information transfer and learning interaction during online learning; 6) encouraging educational innovation during Covid-19 pandemic; 7) Be effective and efficient, both as a product and a process to solve learning problems; 8) Learning medium are not only tools but also as parts, includes strategies and learning methods during Covid-19 pandemic. Sore teachers made various medium, including: 1) use technology devices as well as online media; 2) conduct information and communication technology training; 3) self-taught learning or self-learning about technology development; 4) increase self-potential especially in using technology as a learning medium, as well as applying more interesting methods or models of learning